1992
DOI: 10.1029/92je01865
|View full text |Cite
|
Sign up to set email alerts
|

Mineral equilibria and the high radar reflectivity of Venus mountaintops

Abstract: We studied the relationship between altitude and microwave emissivity (the complement of power reflectivity) in 10 highland regions of Venus, using the Magellan data set. Above a critical altitude that ranges from 4.75 km on Maxwell Montes to 2.49 km on Sapas Mons, emissivity undergoes an abrupt decrease to values so low (<0.6) that the surface mineralogy on these mountaintops must differ from that at lower altitudes in such a way as to enhance the bulk dielectric constant of the highland surface material. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
97
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 38 publications
5
97
0
Order By: Relevance
“…Nevertheless, differences in elevation can produce variations in modification. Laboratory data indicate that both olivine and pyroxene are more unstable in the Venusian lowlands than in the highlands [Fegley et al, 1992;Klose et al, 1992]. Thus, while basaltic minerals can weather at all elevations on Venus, such weathering should be both faster and more intense at lower elevations, and it may diminish significantly with increasing altitude.…”
Section: Surface Weatheringmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, differences in elevation can produce variations in modification. Laboratory data indicate that both olivine and pyroxene are more unstable in the Venusian lowlands than in the highlands [Fegley et al, 1992;Klose et al, 1992]. Thus, while basaltic minerals can weather at all elevations on Venus, such weathering should be both faster and more intense at lower elevations, and it may diminish significantly with increasing altitude.…”
Section: Surface Weatheringmentioning
confidence: 99%
“…On Venus this process seems to be dominated by chemical reactions between atmospheric SO2 or CO2 and iron-bearing silicates [Fegley et al, 1992;Klose et al, 1992]. The primary result is a disintegration of rock surfaces into fine-grained dust which slowly accumulates in local lows to soften radar returns .…”
Section: Surface Weatheringmentioning
confidence: 99%
“…This observed mixing ratio of SO 2 is close to the equilibrium mixing ratio over pyrite-magnetite assemblage (e.g., Zolotov, 1991;Klose et al, 1992) calculated from the observed CO concentration and thermochemical data (Robie et al, 1979;Chase et al, 1985). In the following we call this as the pyrite-magnetite buffer.…”
Section: Introductionmentioning
confidence: 82%
“…An increase in atmospheric SO 2 raises the surface temperature. This positive feedback is suggested by Klose et al (1992), and they concluded that the climate system would not be stabilized. We call this as a chemical-greenhouse feedback.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation